Page Load Time Speed Increase on Disease Outbreak Investigation Information System Website - Rahmat Oktrifianto; Dani Adhipta; Warsun Najib (IJITEE (International Journal of Information Technology and Electrical Engineering), 2019)
Outbreaks or extraordinary events often become an issue that occurs in Indonesia. Therefore, an outbreak investigation information system is required to collect, manage and analyze data quickly and accurately. On the other hand, challenges in data accessing processes in certain locations are still constrained by a slow internet connection. This paper conducted speed increase of a page load or site speed time from disease outbreaks investigation information system website.Page load time speed testing was carried out using Google Chrome Developer Tools and using simulation speeds of 2.5 Mbps. Testing time was carried out by dividing the time into three sections, morning hours, working hours and night hours. Implementation of page load time increase includes reducing HTTP requests, utilizing GZIP compression, performing code minification, setting browser chache, using CDN, and using other enhancement techniques.The results showed that after implementing an increase in page load time by turning off cache and using cache, there was an increase in site speed. When the browser cache was turned off, an average page load time increased of 54.79% from the previous time. Whereas when using the browser cache, page load time speed increased by 55.28% from the previous time.